Impact of an Acute Care Surgery Model on the Management of Acute Appendicitis in South Korea: A Retrospective Cohort Study. (26th March 2021) - Yi, Gun-Hee; Lee, Hak-Jae; Lee, Seul; Yoon, Jong-Hee; Hong, Suk-Kyung
Abstract : Background . The acute care surgery (ACS) system is a new model for the prompt management of diseases that require rapid treatment in patients with acute abdomen. This study compared the outcomes and characteristics of the ACS system and traditional on-call system (TROS) for acute appendicitis in South Korea. Methods . This single-center, retrospective study included all patients (aged ≥18 years) who underwent surgery for acute appendicitis in 2016 and 2018. The TROS and ACS system were used for the 2016 and 2018 groups, respectively. We retrospectively obtained data on each patient from the electrical medical records. The independent samples t -test and Mann–Whitney U -test were used for continuous and nonnormally distributed data, respectively. Results . In total, 126 patients were included. The time taken to get from the emergency room admission to the operating room, operation times, and postoperative complication rates were similar between both groups. However, the length of the hospital stay was shorter in the ACS group than in the TROS group (4.3 ± 3.2 days vs. 7.2 ± 9.6 days, p = 0.039 ). Conclusions . Since the introduction of the ACS system, the length of hospital stay for surgical patients has decreased. This may be due to the application of an integrated medical procedure, such as a new clinical pathway, rather than differences in the surgical techniques.